Biology of Stink Bug (Nezara viridula Linnaes, Hemiptera: Pentatomidae) with Long Beans as a Feed (Vigna sinensis L.) in Laboratory - Muthiah, Fitri; Dr. Ir. Tris Haris Ramadhan, MP, Dr. Ir. Tris Haris Ramadhan, MP; Ir. Indri Hendarti, M.Sc, Ir. Indri Hendarti, M.Sc (Fakultas Pertanian Universitas Tanjungpura, 2019)
Muthiah Fitri (1), Ramadhan Haris. T (2), Hendarti Indri (3)(1) Student of Faculty of Agriculture and (2) Lecturer Staff of Agriculture FacultyUniversity of Tanjungpura Pontianak ABSTRACTStink bug Nezara viridula (L.) is one of the pests that attacks the nuts plantation, including long beans. This study aims to determine the biology of stink bug on the long bean (Vigna sinensis) in the laboratory. The research was conducted in the laboratory of Plant Pest Faculty of Agriculture of Tanjungpura University for about 4 months. Stink bug were rearing in jars that are hollowed under its bottom and covered with gauze, jars are used in reverse. Long bean as a feed was replaced every 2 days. The observations were made on 100 individu as a cohort divided into 10 jars, 1 jar there are 10 individual of stink bugs. The results showed that: the development period of Nezara viridula (L.) from hatching to adult ranged from 25 - 35 days, the stage of eggs ranged between 5 - 9 days. The nymph consists of 5 instars, the duration of first instar stage were (4 - 5 days), second instar were (5 - 11 days), third instar (5 - 12 days), fourth instar (6 - 12 days), and fifth instar (9 - 16 days). The sex ratio of stink bug on the long bean is 1 : 1. The period life of male adult ranged from 1 - 81 days and female adult ranged from 12 - 86 days. Pre-oviposition periods range from 15 - 47 days (average 10.19 days). The post-oviposition period ranges from 2 - 47 days (average 12.50 days). Egg fertility ranges from 0% - 96.47%. Egg height ranges from 0.59 to 0.62 mm. The number of eggs produced ranged from 113 to 780 eggs (an average of 320 eggs). The mortality of the first instar nymph was (20%), second instar (8,75%), third instar (6,84%), fourth instar (13,27%), and fifth instar (27,11%). Keywords: Biology, Long beans (V. sinensis), N. viridula (L)